An Insightful Internship Experience at Bank of Baroda - Ahuja, Sakshi (ATLAS SkillTech University, 2025)
The report delves into comprehensively understanding of the landscape of the banking industry, Bank of Baroda's company dynamics, and personal experiences during the internship at their credit department. It start with understanding of the banking industry, especially with an inclination towards Bank of Baroda and Micro, Small, and Medium Enterprises in India. At a global scale, the banking industry has been going through difficult times related to increased regulatory framework, technological disruptions etc. As a result, banks have already gone through a stage of recovery and adaptation. In India, the banking sector has been strong because of the reformed regulatory environment of the RBI. Growth of fintech industry and initiatives like Pradhan Mantri Jan Dhan Yojana has helped make India a leader in digital payments and financial inclusion. The MSME sector has been struggling by lack of access to proper finances and advance technology, remains the central problems of economic growth in India. Government has been making initiatives and digital practices to foster growth and competitiveness within this sector. Bank of Baroda is one of the major participants in the Indian banking scenario since its inception in 1908 and has an extensive network of branches and offices that span worldwide. The organizational structure of this bank facilitates a broad range of banking services, such as retail, corporate, and international banking.
Project Report on An Insightful Internship Experience at Bank of Baroda (2023-2025) Under the Guidance of Prof. Chetana Asbe
Keywords: technological; Bank of Baroda; extensive network